Study of the practice of female medical students in the prevention of iron deficiency anemia due to menstruation - "Rezaie-pour; A. Yavari; P. Mahmoudi; M. Fili; S. " (Tehran University of Medical Sciences, 2002)
Iron deficiency is the most common nutritional deficiency in the world. Women at childbearing age are at particular risk of developing iron deficiency due to the iron losses associated with menstruation and childbirth. Therefore, iron supplements are needed in certain groups, while in particular regions increased dietary intake could be provided through food. This descriptive study attempts to identify practice among university students of Tehran University of Medical Sciences in the prevention of iron deficiency anemia due to menstruation in the year 1999. This study includes 257 university students of different majors (such as medicine, dentistry, pharmacy, obstetrics, nursing, nutrition, health (occupational, Public) laboratory sciences) of the Tehran University of Medical Sciences who were selected through a simple random sampling method. The pattern of study was a questionnaire consisting of 37 questions, in addition to a chart to determine food consumption frequency. The questionnaire was divided into three sections: demographic data, the status of nutrition, and iron supplementation. To analyze the data descriptive statistics and (2) test were used. The results showed that the most of the samples were in the age group of 21 to 25 years and 36.5% of them stayed in dormitories. Most of the subjects of study had moderate nutrition and some of them had good nutrition. The majority of them (92.5%) were not using the iron supplements during the menstruation period and the duration between two subsequent menses. The results of the research show that the function of 35.2 % of the subjects of study in relation to the prevention of iron deficiency was weak, 53.9% of them were moderate and only 10.9% of them were good. The statistical test (2) which was used to analyze the results obtained, showed a significant relationship between the practice of the subjects and their living in a dorms (P<0.001). In conclusion, the application of the results for further researches and also for practical use has been proposed.